2020
DOI: 10.1002/agj2.20394
|View full text |Cite
|
Sign up to set email alerts
|

Field and model assessments of irrigated soybean responses to increased air temperature

Abstract: Correctly quantifying elevated air temperature effects on crop yield through field experiments and crop modeling is essential for developing adaptation strategies under climate change. In this study, the effects of elevated air temperature on soybean [Glycine max (L.) Merr.] production were investigated using a four-year open top chamber experiment (2015-2018) in North Carolina, USA. The experimental results showed that an increase of average air temperature during growing seasons by 3.4 • C to 25.7 • C decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
4
13
0
Order By: Relevance
“…RCP = Representative Concentration Pathways, RE = CO 2 factor to leaf quantum efficiency, QE = quantum efficiency T A B L E 1 Calibrated soybean cultivar parameters in CROPGRO-Soybean. (Sima et al, 2020) HERMES (20%), with an ensemble reduction of 13% that was close to observed 11% decrease. CROPGRO simulated maturity dates were closer to experimental results than that of HERMES.…”
Section: Model Overviewsupporting
confidence: 76%
See 4 more Smart Citations
“…RCP = Representative Concentration Pathways, RE = CO 2 factor to leaf quantum efficiency, QE = quantum efficiency T A B L E 1 Calibrated soybean cultivar parameters in CROPGRO-Soybean. (Sima et al, 2020) HERMES (20%), with an ensemble reduction of 13% that was close to observed 11% decrease. CROPGRO simulated maturity dates were closer to experimental results than that of HERMES.…”
Section: Model Overviewsupporting
confidence: 76%
“…Although the CROPGRO and HERMES modules use different CO 2 assimilation algorithms and temperature response functions (Figure 1; Sima et al, 2020), both produced similar responses of soybean yield to climate change scenarios under RCP4.5 and RCP8.5 (Figures 3 and 4), which was consistent with previous results on evaluating several CO 2 assimilation algorithms with FACE experiments (Nendel et al, 2009). Under rainfed conditions, however, CROPGRO simulated greater climate change effects on seed yield and biomass than HERMES under both RCP4.5 (50 vs. 26%) and RCP8.5 (55 vs. 22%), indicating greater sensitivity of CROPGRO to 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations